Does the judiciary provide adequate control over subsidiary legislation / Norainy Shahar Alam - Hussein, Norashikin (1981)
in view of the alarmingly rate of subsidiary legislation enacted per year, there is a greater need for control over the subsidiary legislation so that the executive will no readily abuse the powers vested on to them according to their unfettered and unlimited discretion. This is more so if the legislation tend to encroach upon matters such as rights, liberty and property of an individual.